2010
DOI: 10.2214/ajr.10.4376
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Radiology Chairpersons' Perceptions of the Relative Importance of Education of Medical Students, Residents, and Fellows

Abstract: Resident education as a valued activity and as a specific chair function varies inversely with both program size and the percentage of fellows among all trainees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…A recent report highlighted the opinions of Radiology department chairpersons' regarding the weighted importance of resident and fellow education among other departmental success metrics via a survey questionnaire sent to all American members of the Society of Chairmen in Academic Radiology (SCARD) [6]. Sixtyfour percent of chairpersons responded and were asked to weigh the relative importance of various components of department growth such as clinical research, faculty Lowest rated components of fellowship training included lack of curriculum (57%), lack of structured learning (48%) and lack of mentoring (24%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent report highlighted the opinions of Radiology department chairpersons' regarding the weighted importance of resident and fellow education among other departmental success metrics via a survey questionnaire sent to all American members of the Society of Chairmen in Academic Radiology (SCARD) [6]. Sixtyfour percent of chairpersons responded and were asked to weigh the relative importance of various components of department growth such as clinical research, faculty Lowest rated components of fellowship training included lack of curriculum (57%), lack of structured learning (48%) and lack of mentoring (24%).…”
Section: Discussionmentioning
confidence: 99%
“…Turnover among program directors is a "current/impending" p r o b l e m a n d t h e m a j o r i t y o f respondents felt that time spent on documentation detracted from teaching, learning and taking care of patients. Baker et al [6] To survey radiology chairpersons' views about the value of education with respect to department success a n d t o r e p o r t t h e i r d i r e c t involvement in the educational process…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical qualifications for a department chair include being a strong role model and exhibiting excellence in teaching and all types of professional work. 12 Chairs themselves perceive that they are role models, [13][14][15] and many are directly involved in the training of residents. 15 Family medicine faculty act as role models to trainees and influence them in a variety of ways.…”
Section: Introductionmentioning
confidence: 99%
“…12 Chairs themselves perceive that they are role models, [13][14][15] and many are directly involved in the training of residents. 15 Family medicine faculty act as role models to trainees and influence them in a variety of ways. One study of primary care faculty showed that medical students' Family physicians are trained broadly to provide the majority of health care across multiple settings; however, their scope of practice has narrowed.…”
Section: Introductionmentioning
confidence: 99%